Cinematic Imaging and Imagining through the Lens of Buddhism. Issue 3 (November 2020) - Fan, Victor
Abstract : The oft-undiscernible boundary between imaging and imagining is especially apparent in our cinematic experience. In Buddhist philosophy, imaging and imagining are neither the same nor different, neither not the same nor not different. In this article, I argue that imaging in Buddhism refers not only to the formational process of an image (external form) out there, but also the external form's interdependent relationship with the internal forms (sensory organs). Likewise, imagining refers not only to the formational process of an image in here, but also to how these imaginations constitute the body's relationship with the larger milieu out there. In the second half of this article, I analyse how the interdependent relationship between imaging and imagining is configured textually and in the overall cinematic experience in Bi Gan's Diqiu zuihou de yewan / Long Day's Journey into Night (2018).